DILEMA YURIDIS KLAUSULA EKSONERASI: ANTARA KEPASTIAN HUKUM PENGELOLA PARKIR DAN KEADILAN BAGI KONSUMEN - Hikmawati; Hasdar (Jurnal Hukum Cassowary, 2025)
This study aims to analyze the legal validity of exoneration clauses in parking tickets that transfer liability for loss to consumers, and to reconstruct the legal relationship between operators and service users. The research method employed is normative juridical with a statutory approach and case analysis of Supreme Court jurisprudence. The results indicate that the legal relationship in modern parking is qualified as a custody agreement (bewaring), not land lease, implying a mandatory duty of care. It was found that the standard clause stating "loss is not the management's responsibility" violates Article 18 of the Consumer Protection Law, rendering it null and void. In conclusion, parking operators are fully liable for the loss of consumer vehicles based on the principle of vicarious liability, and cannot evade this obligation through the inclusion of unilateral clauses that disadvantage the consumer's bargaining position.